The Effect of Intermittent Preventive Treatment of Malaria During Pregnancy and Placental Malaria on Infant Risk of Malaria. (3rd July 2021) - Andronescu, Liana R; Sharma, Ankur; Peterson, Ingrid; Kachingwe, Martin; Kachepa, Witness; Liang, Yuanyuan; Gutman, Julie R; Mathanga, Don P; Chinkhumba, Jobiba; Laufer, Miriam K
Abstract: Background: Intermittent preventive treatment of malaria during pregnancy (IPTp) with dihydroartemisinin-piperaquine (DP) provides greater protection from placental malaria than sulfadoxine-pyrimethamine (SP). Some studies suggest placental malaria alters risk of malaria infection in infants, but few have quantified the effect of IPTp on infant susceptibility to malaria. Methods: Infants born to women enrolled in a randomized clinical trial comparing IPTp-SP and IPTp-DP in Malawi were followed from birth to 24 months to assess effect of IPTp and placental malaria on time to first malaria episode and Plasmodium falciparum incidence. Results: In total, 192 infants born to mothers randomized to IPTp-SP and 195 randomized to IPTp-DP were enrolled. Infants in IPTp exposure groups did not differ significantly regarding incidence of clinical malaria (incidence rate ratio [IRR], 1.03; 95% confidence interval [CI], .58–1.86) or incidence of infection (IRR, 1.18; 95% CI, .92–1.55). Placental malaria exposure was not associated with incidence of clinical malaria (IRR, 1.03; 95% CI, .66–1.59) or infection (IRR, 1.15; 95% CI, .88–1.50). Infant sex, season of birth, and maternal gravidity did not confound results. Conclusions: We did not find evidence that IPTp regimen or placental malaria exposure influenced risk of malaria during infancy in this population. Clinical Trials Registration . NCT03009526 Abstract : In a cohort of infants born to mothers randomized to receive sulfadoxine-pyrimethamine or dihydroartemisinin-piperaquine to prevent malaria during pregnancy, we found no impact of maternal drug regimen on the risk of P. falciparum infection or clinical malaria.